1997
DOI: 10.1007/s004180050130
|View full text |Cite
|
Sign up to set email alerts
|

Type X collagen expression and hypertrophic differentiation in chondrogenic neoplasias

Abstract: Little is known about matrix biochemistry and cell differentiation patterns in chondrogenic neoplasms. This is the first description of the focal expression of collagen type X by neoplastic chondrocytes in situ and its incorporation into the extracellular matrix of cartilaginous tumors. This shows that neoplastic chondrocytes have the potential to undergo the full program of cell differentiation, including hypertrophy, comparable to their physiological counterparts in the growth plate. However, only in benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
2
35
1
Order By: Relevance
“…Myxoid areas of conventional chondrosarcomas strongly express aggrecan 34,43 and, at least focally, collagen types II and X, features not seen in extraskeletal myxoid chondrosarcoma. 24,34 The difference between these two types of neoplasms is also evident at the genetic level. Myxoid variants of skeletal chondrosarcomas do not show the chromosomal translocations found typically in extraskeletal myxoid chondrosarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myxoid areas of conventional chondrosarcomas strongly express aggrecan 34,43 and, at least focally, collagen types II and X, features not seen in extraskeletal myxoid chondrosarcoma. 24,34 The difference between these two types of neoplasms is also evident at the genetic level. Myxoid variants of skeletal chondrosarcomas do not show the chromosomal translocations found typically in extraskeletal myxoid chondrosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the relationship between extraskeletal and skeletal myxoid chondrosarcoma is unclear, 3 and molecular and ultrastructural evidence suggests both being completely different tumor entities. 3,18 Chondrogenic differentiation in fetal development, 20,21 in adult secondary chondrogenesis, 22 and in chondrogenic neoplasms [23][24][25][26] can be identified and monitored by investigating marker genes of chondrocytic differentiation such as collagen subtypes. In particular, collagen types II and X are distinct markers for the chondrocytic cell lineage (for a review see Cancedda et al 27 ).…”
mentioning
confidence: 99%
“…24 Immunohistochemistry was performed for proliferation rate analysis using a monoclonal antibody against Ki-67 (clone MIB1, 1:100; Dako, Glostrup, Germany) according to standard laboratory procedures. 25 …”
Section: Histopathological and Immunohistochemistry Evaluationmentioning
confidence: 99%
“…Histochemical and immunohistochemical analyses have shown that chondrosarcomas showing mainly mature and terminally differentiated (hypertrophic) chondrocytic phenotypes display only scant proliferation, whereas less differentiated chondrosarcomas with the phenotype of dedifferentiated chondrocytes show significantly higher proliferative activity (4). These features are highly correlated with prognosis (5). These findings suggest the possibility that the induction of differentiation in chondrosarcoma cells could lead to a novel therapeutic strategy.…”
mentioning
confidence: 98%